THE ROLE OF LEADERSHIP AND ORGANIZATIONAL CULTURE IN IMPROVING EMPLOYEE PERFORMANCE AT PT GOLD EMPEROR DUA - Nofi Nur Afianti; Fakhruddin Kurnia M (Jurnal Mahasiswa Manajemen, 2025)
This study aims to determine and examine the Role of Leadership and Organizational Culture in improving employee performance at PT Gold Emperor Dua. Leadership and organizational culture are two important factors that can effect employee performance in an organization. Effective leadership can motivate and inspire employees to achieve organizational goals, while a strong organizational culture can shape positive employees values and behavior. This study is a qualitative descriptive study with a case study approach. The presentation of data is done descriptively, and the data obtained is based on the result o field observations using interview techniques. The results to the study indicate that the Role of Leadership and Organizational Culture have a significant positive effect on Employee Performance.